High-strength wear-resistant refractory castable and preparation method thereof
By preparing high-strength wear-resistant refractory castables, using silicon carbide micro powder and steel fiber reinforcement phases, and combining lithium chloride to control the hydration reaction, the problems of difficult control of the hydration process and insufficient performance of existing wear-resistant refractory castables have been solved. This has achieved high compressive strength and excellent high-temperature wear resistance, while reducing production costs.
Patent Information
- Application Number
- CN202511426470.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-30
- Publication Date
- 2025-12-30
AI Technical Summary
Existing wear-resistant and refractory castables suffer from problems such as difficulty in controlling the hydration process, high cost, insufficient mid-temperature strength, low compressive strength, and insufficient high-temperature wear resistance.
High-strength, wear-resistant, and refractory castables are prepared by using raw materials such as α-active alumina micro powder, silicon carbide micro powder, white corundum micro powder, and aluminate cement, combined with steel fiber and lithium chloride micro powder, through ball milling and dry mixing processes. The particle size of the powder and the hydration reaction path are controlled to form a dense matrix and a stable bonding phase.
The prepared high-strength wear-resistant refractory castable has high compressive strength, excellent high-temperature wear resistance and controllable medium-temperature strength, which reduces production costs.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of wear-resistant refractory materials. Specifically, it relates to a high-strength wear-resistant refractory castable and a preparation method thereof. TECHNICAL BACKGROUND With the transformation of manufacturing industry towards high quality development, traditional industries such as metallurgy, energy and construction are accelerating the transformation towards green, intelligent and high-end. The production equipment in these key fields is generally threatened by the erosion and wear of solid particles under high temperature conditions. The existing refractory castables have problems such as poor high-temperature volume stability, decreased bonding strength after heat treatment due to the difference in thermal expansion coefficient between aggregates and matrix, and inability to cope with high-temperature working conditions, which seriously restricts the continuity of device operation. The technical personnel in this field have continuously researched on this problem: The patent technology "High-alumina high-temperature refractory castable and preparation method" (ZL201210247677.6) has the advantages of high overall compactness and high-temperature resistance, but has the problem of insufficient high-temperature wear resistance due to the decomposition of hydrates.
[0002] The patent technology "High-wear-resistant quick-drying refractory castable and preparation method thereof" (CN201811592665.0) has good combination performance with the original lining, short oven time and fast heating speed when used to make the lining, but has the problem of insufficient medium-temperature strength before the formation of ceramic phase.
[0003] The patent technology "Al2O3-SiC-C refractory castable and preparation method thereof" (CN202010487302.1) has the advantages of high cold strength, good erosion resistance and thermal shock stability, but has the problems of poor bonding strength between silicon carbide and matrix and easy wear resistance decline due to carbon oxidation and burning loss.
[0004] The patent technology "ZrO2-(Al,Cr)2O3-Mg(Al,Cr)2O4 composite refractory material and preparation method thereof" (CN202311144852.3) has the characteristics of high strength, high toughness and long service life, but the regulation and control of phase transformation during the hydration process of the castable in this composite system is high and the cost is high.
[0005] In summary, the existing wear-resistant refractory castables have the following technical defects: difficult to control the hydration process, high cost, insufficient medium-temperature strength, low compressive strength, and high-temperature wear resistance to be improved. SUMMARY
[0006] The application aims at overcoming the technical defects of the prior art, and aims to provide a preparation method of high-strength wear-resistant refractory castable with low cost.
[0007] To achieve the above-mentioned purpose, the technical solution adopted by the application has the following specific steps: Step 1: 5-7 parts by mass of α-active alumina micro powder, 5-7 parts by mass of silicon carbide micro powder, 4-5 parts by mass of silicon dioxide micro powder and 9-12 parts by mass of white corundum micro powder are added into a ball mill tank, and ball milling is carried out at a rotating speed of 45-50 rpm for 3-6 hours, and then screening is carried out to obtain premixed powder with a particle size of less than 45 μm.
[0008] Step 2: 0.1-0.15 parts by mass of sodium tripolyphosphate, 0.05-0.1 parts by mass of sodium hexametaphosphate, 0.05-0.1 parts by mass of FDN, 0.4-0.45 parts by mass of lithium chloride micro powder and 8-14 parts by mass of aluminate cement are added into a ball mill tank, and ball milling is carried out at a rotating speed of 45-50 rpm for 3-6 hours to obtain premixed cement.
[0009] Step 3: 20-25 parts by mass of bauxite particles with a particle size of 3-5 mm, 25-30 parts by mass of bauxite particles with a particle size of 1-3 mm and 10-15 parts by mass of bauxite particles with a particle size of less than 1 mm are added into a stirring pot, and dry mixing is carried out to obtain premixed aggregate.
[0010] Step 4: the premixed cement and the premixed powder are added into the premixed aggregate, 1-2 parts by mass of steel fiber is further added, and dry mixing is continued for 120-180 seconds to obtain high-strength wear-resistant refractory castable.
[0011] The particle size of the α-active alumina micro powder is less than 1 μm; and the Al2O3 content of the α-active alumina micro powder is greater than or equal to 99.5 wt%.
[0012] The particle size of the silicon carbide micro powder is less than 50 μm; and the SiC content of the silicon carbide micro powder is greater than or equal to 95 wt%.
[0013] The particle size of the silicon dioxide micro powder is less than 0.15 μm; and the SiO2 content of the silicon dioxide micro powder is greater than or equal to 85 wt%.
[0014] The white corundum micro powder is plate-shaped white corundum or electro-melted white corundum, the particle size of the white corundum micro powder is less than or equal to 75 μm, and the Al2O3 content of the white corundum micro powder is greater than or equal to 99 wt%.
[0015] The particle size of the lithium chloride micro powder is less than or equal to 150 μm, and the LiCl content of the lithium chloride micro powder is greater than or equal to 99 wt%.
[0016] The alkaline particles contain more than 85 wt% Al2O3.
[0017] The aluminate cement has the following characteristics: particle size < 45 μm, proportion < 8 wt%, and refractoriness of 1420~1460℃; Al2O3 content ≥ 51 wt% and CaO content ≥ 33.5 wt%.
[0018] The steel fiber is a single, loose type, without coating, straight longitudinally, with hooks at both ends, smooth surface, length of 27~33mm, equivalent diameter of 0.28~0.32mm, and tensile strength of 1000~1300Mpa.
[0019] By adopting the above technical solution, the present invention has the following advantages compared with the prior art: (1) This invention introduces silicon carbide micropowder and steel fiber reinforcing phase simultaneously. The dense matrix formed by the silicon carbide micropowder, combined with the excellent toughness and bridging effect of the steel fiber, improves the mechanical anchoring ability of the steel fiber and results in high compressive strength. Furthermore, the excellent thermal conductivity of the steel fiber improves the overall thermal conductivity of the high-strength wear-resistant refractory castable, alleviating the interfacial stress caused by thermal expansion mismatch during heat treatment and at high temperatures, and promoting tight interfacial bonding. By adding silicon carbide micropowder and steel fiber composite into the castable, combined with the strong ceramic bonding phase synthesized in situ in the matrix, the high-strength wear-resistant refractory castable is endowed with excellent properties. Therefore, the prepared high-strength wear-resistant refractory castable has high compressive strength and excellent structural stability.
[0020] (2) This invention avoids the phenomenon of small-scale, low-degree early hydration reactions of cement particles that bind a certain amount of environmental water molecules through physical adsorption in the industrial environment by premixing the powder materials other than cement. Screening the powder after ball milling removes a small amount of agglomerates that may form during the ball milling process, ensuring precise control of the powder particle size. After adding water, a uniform slurry can be quickly formed, resulting in lower water requirements during casting. Further mixing with aluminate cement ensures that cement, as the cementing phase, is uniformly distributed throughout the system. This uniform phase distribution provides the high-strength, wear-resistant, and refractory castable with a more controllable hardening process, higher bulk density and strength, and superior high-temperature wear resistance.
[0021] (3) This invention premixes lithium chloride with aluminate cement, causing the cement particles to be uniformly coated with lithium chloride. During the hydration reaction, a large amount of lithium ions are released into the water, reacting rapidly with dissolved aluminate ions to form an unstable, water-insoluble intermediate phase. This intermediate phase then decomposes in an alkaline environment rich in calcium ions to generate crystal nuclei, precisely controlling the hydration path of the aluminate cement to directly generate a stable C3AH6 phase. The biggest hidden danger of traditional processes is the formation of a large number of metastable hydration products. When the subsequent temperature exceeds 30-35°C, a reaction occurs, leading to a significant decrease in intermediate-temperature strength. The high-strength, wear-resistant, and refractory castable prepared by this invention will not experience strength degradation due to crystal transformation throughout its entire service life. The microstructure of the stable C3AH6 phase has a more uniform and interconnected pore distribution, greatly improving the strength and wear resistance of the high-strength, wear-resistant, and refractory castable. At the same time, the hydration reaction during the curing process is controllable, resulting in low production costs. The prepared high-strength, wear-resistant, and refractory castable has excellent intermediate-temperature strength.
[0022] Water was added to the prepared high-strength wear-resistant refractory castable at a mass ratio of 100:4, mixed thoroughly, cast into molds, cured at room temperature, and dried at 110℃ for 24 hours. The service temperature range is 900~1100℃. The main properties of the high-strength wear-resistant refractory castable were tested: wear resistance ≤2.5cm. 3 (900℃×3h); Compressive strength at room temperature ≥75MPa after heat treatment at 110℃; ≥125MPa after heat treatment at 900~1100℃; Flexural strength at room temperature ≥15MPa after heat treatment at 110℃; ≥18MPa after heat treatment at 900~1100℃; Thermal shock resistance ≥30 cycles (900℃, water cooling); Permanent linear change after heating ±0.5% (1000℃×3h); Thermal conductivity ≥6W·(m·K) -1 (1000℃); Bulk density ≥2.6 g·cm³ -3 .
[0023] Therefore, the production cost of this invention is low, and the high-strength wear-resistant refractory castable prepared by this invention has the characteristics of high compressive strength, excellent high-temperature wear resistance, high medium-temperature strength, and controllable hydration process. Detailed Implementation
[0024] The present invention will be further described below with reference to specific implementation methods, but this is not intended to limit the scope of protection thereof.
[0025] A high-strength, wear-resistant, and refractory castable and its preparation method. The preparation method described in this specific embodiment is as follows: Step 1: Add 5-7 parts by weight of α-active alumina micro powder, 5-7 parts by weight of silicon carbide micro powder, 4-5 parts by weight of silica micro powder and 9-12 parts by weight of white corundum micro powder into a ball mill jar, and ball mill for 3-6 hours at a speed of 45-50 rpm. After sieving, obtain a premixed powder with a particle size <45μm.
[0026] Step 2: Add 0.1-0.15 parts by weight of sodium tripolyphosphate, 0.05-0.1 parts by weight of sodium hexametaphosphate, 0.05-0.1 parts by weight of FDN, 0.4-0.45 parts by weight of lithium chloride micro powder and 8-14 parts by weight of aluminate cement into a ball mill jar, and ball mill at a speed of 45-50 rpm for 3-6 hours to obtain premixed cement.
[0027] Step 3: Add 20-25 parts by weight of bauxite particles with a particle size of 3-5 mm, 25-30 parts by weight of bauxite particles with a particle size of 1-3 mm, and 10-15 parts by weight of bauxite particles with a particle size of <1 mm to a mixing pot and dry mix to obtain premixed aggregate.
[0028] Step 4: Add the premixed cement and the premixed powder to the premixed aggregate, then add 1-2 parts by weight of steel fiber, and continue dry mixing for 120-180 seconds to obtain a high-strength wear-resistant refractory castable.
[0029] The Al2O3 content of the α-active alumina micro powder is ≥99.5wt%.
[0030] The SiC content in the silicon carbide micro powder is ≥95wt%.
[0031] The silica micro powder has a SiO2 content of ≥85wt%.
[0032] The white fused alumina powder is tabular white fused alumina or fused white fused alumina, and the Al2O3 content of the white fused alumina powder is ≥99wt%.
[0033] The lithium chloride micro powder has a LiCl content of ≥99wt%.
[0034] The alkaline particles contain more than 85 wt% Al2O3.
[0035] The aluminate cement has an Al2O3 content ≥ 51 wt% and a CaO content ≥ 33.5 wt%.
[0036] In this specific implementation: The particle size of the α-active alumina micro powder is <1 μm; The particle size of the silicon carbide micro powder is <50μm; The particle size of the silica micro powder is <0.15μm; The particle size of the white corundum micro powder is ≤75μm; The lithium chloride micro powder has a CAS particle size ≤150μm; The aluminate cement has a particle size <45μm and a proportion <8wt%; the aluminate cement has a refractoriness of 1420~1460℃; The steel fibers are single, bulk type, uncoated, straight longitudinally, hooked at both ends, smooth surface, length in the range of 27~33mm, equivalent diameter in the range of 0.28~0.32mm, and tensile strength in the range of 1000~1300Mpa.
[0037] The details will not be repeated in the examples.
[0038] Example 1 A high-strength, wear-resistant, and refractory castable and its preparation method. The preparation method described in this embodiment is as follows: Step 1: Add 7 parts by weight of α-active alumina micro powder, 7 parts by weight of silicon carbide micro powder, 4 parts by weight of silica micro powder and 12 parts by weight of white corundum micro powder into a ball mill jar, and ball mill for 3 hours at a speed of 45 rpm. After sieving, a premixed powder with a particle size of <45 μm is obtained.
[0039] Step 2: Add 0.1 parts by weight of sodium tripolyphosphate, 0.05 parts by weight of sodium hexametaphosphate, 0.05 parts by weight of FDN, 0.4 parts by weight of lithium chloride micro powder and 8 parts by weight of aluminate cement into a ball mill jar, and ball mill at 45 rpm for 3 hours to obtain premixed cement.
[0040] Step 3: Add 22 parts by weight of bauxite particles with a particle size of 3-5 mm, 30 parts by weight of bauxite particles with a particle size of 1-3 mm, and 10 parts by weight of bauxite particles with a particle size of <1 mm into a mixing pot and dry mix to obtain premixed aggregate.
[0041] Step 4: Add the premixed cement and the premixed powder to the premixed aggregate, then add 1 part by weight of steel fiber, and continue dry mixing for 120 seconds to obtain a high-strength wear-resistant refractory castable.
[0042] In this example: The α-active alumina micro powder has an Al2O3 content of 99.5 wt%.
[0043] The silicon carbide micro powder has a SiC content of 95 wt%.
[0044] The silica micro powder has a SiO2 content of 85 wt%.
[0045] The white fused alumina powder is tabular white fused alumina, and the Al2O3 content of the white fused alumina powder is 99wt%.
[0046] The lithium chloride micro powder has a LiCl content of 99 wt%.
[0047] The chemical composition of the bauxite particles contains 85 wt% Al2O3.
[0048] The aluminate cement has an Al₂O₃ content of 51 wt% and a CaO content of 33.5 wt%. Water was added to the high-strength, wear-resistant, refractory castable at a mass ratio of 100:4, and mixed thoroughly. The mixture was then cast into molds, cured at room temperature, dried at 110℃ for 24 hours, and the service temperature was 900℃. The main properties of the high-strength, wear-resistant, refractory castable were tested: abrasion resistance of 2.34 cm. 3 (900℃×3h); room temperature compressive strength after heat treatment at 110℃ is 78 MPa; after heat treatment at 900℃ it is 125 MPa; room temperature flexural strength after heat treatment at 110℃ is 15.3 MPa; after heat treatment at 900℃ it is 18.4 MPa; thermal shock resistance is 31 cycles (900℃, water cooling); permanent linear change upon heating is -0.42% (1000℃×3h); thermal conductivity is 6.1 W·(m·K). -1 (1000℃); Bulk density is 2.68 g·cm³ -3 .
[0049] Example 2 A high-strength, wear-resistant, and refractory castable and its preparation method. The preparation method described in this embodiment is as follows: Step 1: Add 5 parts by weight of α-active alumina micro powder, 5 parts by weight of silicon carbide micro powder, 5 parts by weight of silica micro powder and 11 parts by weight of white corundum micro powder into a ball mill jar, and ball mill for 4 hours at a speed of 47 rpm. After sieving, a premixed powder with a particle size of <45 μm is obtained.
[0050] Step 2: Add 0.12 parts by weight of sodium tripolyphosphate, 0.07 parts by weight of sodium hexametaphosphate, 0.07 parts by weight of FDN, 0.42 parts by weight of lithium chloride micro powder and 12 parts by weight of aluminate cement into a ball mill jar, and ball mill at 47 rpm for 4 hours to obtain premixed cement.
[0051] Step 3: Add 20 parts by weight of bauxite particles with a particle size of 3-5 mm, 27 parts by weight of bauxite particles with a particle size of 1-3 mm, and 15 parts by weight of bauxite particles with a particle size of <1 mm into a mixing pot and dry mix to obtain premixed aggregate.
[0052] Step 4: Add the premixed cement and the premixed powder to the premixed aggregate, then add 1.5 parts by weight of steel fiber, and continue dry mixing for 135 seconds to obtain a high-strength wear-resistant refractory castable.
[0053] In this example: The α-active alumina micro powder has an Al2O3 content of 99.6 wt%.
[0054] The silicon carbide micro powder has a SiC content of 95.5 wt%.
[0055] The silica micropowder has a SiO2 content of 86 wt%.
[0056] The white fused alumina powder is fused white fused alumina, and the Al2O3 content of the white fused alumina powder is 99.1 wt%.
[0057] The chemical composition of the bauxite particles contains 85.5 wt% Al2O3.
[0058] The lithium chloride micro powder has a LiCl content of 99.1 wt%.
[0059] The aluminate cement has an Al₂O₃ content of 51.5 wt% and a CaO content of 33.7 wt%. Water was added to the high-strength, wear-resistant, and refractory castable at a mass ratio of 100:4 (high-strength, wear-resistant, and refractory castable), mixed thoroughly, cast into molds, cured at room temperature, dried at 110℃ for 24 hours, and the service temperature was 1000℃. The main properties of the high-strength, wear-resistant, and refractory castable were tested: wear resistance was 2.13 cm. 3 (900℃×3h). Compressive strength at room temperature after heat treatment at 110℃ is 82 MPa; after heat treatment at 1000℃, it is 131 MPa. Flexural strength at room temperature after heat treatment at 110℃ is 15.6 MPa; after heat treatment at 1000℃, it is 16.4 MPa. Thermal shock resistance is 30 cycles (900℃, water cooling). Permanent linear change upon heating is -0.37% (1000℃×3h). Thermal conductivity is 6.5 W·(m·K). -1 (1000℃); Bulk density is 2.81 g·cm³ -3 .
[0060] Example 3 A high-strength, wear-resistant, and refractory castable and its preparation method. The preparation method described in this embodiment is as follows: Step 1: Add 6 parts by weight of α-active alumina micro powder, 6 parts by weight of silicon carbide micro powder, 4.5 parts by weight of silica micro powder and 10 parts by weight of white corundum micro powder into a ball mill jar, and ball mill for 5 hours at a speed of 49 rpm. After sieving, a premixed powder with a particle size of <45 μm is obtained.
[0061] Step 2: Add 0.14 parts by weight of sodium tripolyphosphate, 0.09 parts by weight of sodium hexametaphosphate, 0.09 parts by weight of FDN, 0.44 parts by weight of lithium chloride micro powder and 14 parts by weight of aluminate cement into a ball mill jar, and ball mill at 49 rpm for 5 hours to obtain premixed cement.
[0062] Step 3: Add 24 parts by weight of bauxite particles with a particle size of 3-5 mm, 26 parts by weight of bauxite particles with a particle size of 1-3 mm, and 12 parts by weight of bauxite particles with a particle size of <1 mm into a mixing pot and dry mix to obtain premixed aggregate.
[0063] Step 4: Add the premixed cement and the premixed powder to the premixed aggregate, then add 1.7 parts by weight of steel fiber, and continue dry mixing for 150 seconds to obtain a high-strength wear-resistant refractory castable.
[0064] In this example: The α-active alumina micro powder has an Al2O3 content of 99.65 wt%.
[0065] The silicon carbide micro powder has a SiC content of 96 wt%.
[0066] The silica micropowder has a SiO2 content of 87 wt%.
[0067] The white fused alumina powder is tabular white fused alumina, and the Al2O3 content of the white fused alumina powder is 99.2 wt%.
[0068] The chemical composition of the bauxite particles contains 86 wt% Al2O3.
[0069] The lithium chloride micro powder has a LiCl content of 99.2 wt%.
[0070] The aluminate cement has an Al₂O₃ content of 51.7 wt% and a CaO content of 33.8 wt%. Water was added to the high-strength, wear-resistant, and refractory castable at a mass ratio of 100:4 (high-strength, wear-resistant, and refractory castable), mixed thoroughly, cast into molds, cured at room temperature, dried at 110℃ for 24 hours, and the service temperature was 1050℃. The main properties of the high-strength, wear-resistant, and refractory castable were tested: wear resistance was 2.27 cm. 3 (900℃×3h). Compressive strength at room temperature after heat treatment at 110℃ is 83 MPa; after heat treatment at 1050℃, it is 137 MPa. Flexural strength at room temperature after heat treatment at 110℃ is 15.5 MPa; after heat treatment at 1050℃, it is 17.4 MPa. Thermal shock resistance is 30 cycles (900℃, water cooling). Permanent linear change upon heating is -0.25% (1000℃×3h). Thermal conductivity is 6.3 W·(m·K).-1 (1000℃); Bulk density is 2.88 g·cm³ -3 .
[0071] Example 4 A high-strength, wear-resistant, and refractory castable and its preparation method. The preparation method described in this embodiment is as follows: Step 1: Add 5.5 parts by weight of α-active alumina micro powder, 5.5 parts by weight of silicon carbide micro powder, 4.7 parts by weight of silica micro powder and 9 parts by weight of white corundum micro powder into a ball mill jar, and ball mill at 50 rpm for 6 hours. After sieving, a premixed powder with a particle size <45 μm is obtained.
[0072] Step 2: Add 0.15 parts by weight of sodium tripolyphosphate, 0.1 parts by weight of sodium hexametaphosphate, 0.1 parts by weight of FDN, 0.45 parts by weight of lithium chloride micro powder and 10 parts by weight of aluminate cement into a ball mill jar, and ball mill at 50 rpm for 6 hours to obtain premixed cement.
[0073] Step 3: Add 25 parts by weight of bauxite particles with a particle size of 3-5 mm, 25 parts by weight of bauxite particles with a particle size of 1-3 mm, and 14 parts by weight of bauxite particles with a particle size of <1 mm into a mixing pot and dry mix to obtain premixed aggregate.
[0074] Step 4: Add the premixed cement and the premixed powder to the premixed aggregate, then add 2 parts by weight of steel fiber, and continue dry mixing for 180 seconds to obtain a high-strength wear-resistant refractory castable.
[0075] In this example: The α-active alumina micro powder has an Al2O3 content of 99.7 wt%.
[0076] The silicon carbide micro powder has a SiC content of 96.5 wt%.
[0077] The silica micro powder has a SiO2 content of 88 wt%.
[0078] The white fused alumina powder is fused white fused alumina, and the Al2O3 content of the white fused alumina powder is 99.3 wt%.
[0079] The chemical composition of the bauxite particles contains 87 wt% Al2O3.
[0080] The lithium chloride micro powder has a LiCl content of 99.3 wt%.
[0081] The aluminate cement has an Al2O3 content of 52 wt% and a CaO content of 33.9 wt%. Water was added to the high-strength wear-resistant refractory castable at a mass ratio of 100:4 (high-strength wear-resistant refractory castable to water), mixed thoroughly, cast into molds, cured at room temperature, dried at 110℃ for 24 hours, and the service temperature was 1100℃. The main properties of the high-strength wear-resistant refractory castable were tested: wear resistance was 1.87 cm. 3 (900℃×3h). Compressive strength at room temperature after heat treatment at 110℃ is 92 MPa; after heat treatment at 1100℃, it is 138 MPa. Flexural strength at room temperature after heat treatment at 110℃ is 16 MPa; after heat treatment at 1100℃, it is 17.8 MPa. Thermal shock resistance is 30 cycles (900℃, water cooling). Permanent linear change upon heating is -0.37% (1000℃×3h). Thermal conductivity is 6.2 W·(m·K). -1 (1000℃); Bulk density is 2.93 g·cm³ -3 .
[0082] This specific implementation method has the following advantages compared with the prior art: (1) This invention introduces silicon carbide micropowder and steel fiber reinforcing phase simultaneously. The dense matrix formed by the silicon carbide micropowder, combined with the excellent toughness and bridging effect of the steel fiber, improves the mechanical anchoring ability of the steel fiber and results in high compressive strength. Furthermore, the excellent thermal conductivity of the steel fiber improves the overall thermal conductivity of the high-strength wear-resistant refractory castable, alleviating the interfacial stress caused by thermal expansion mismatch during heat treatment and at high temperatures, and promoting tight interfacial bonding. By adding silicon carbide micropowder and steel fiber composite into the castable, combined with the strong ceramic bonding phase synthesized in situ in the matrix, the high-strength wear-resistant refractory castable is endowed with excellent properties. Therefore, the prepared high-strength wear-resistant refractory castable has high compressive strength and excellent structural stability.
[0083] (2) This invention avoids the phenomenon of small-scale, low-degree early hydration reactions of cement particles that bind a certain amount of environmental water molecules through physical adsorption in the industrial environment by premixing the powder materials other than cement. Screening the powder after ball milling removes a small amount of agglomerates that may form during the ball milling process, ensuring precise control of the powder particle size. After adding water, a uniform slurry can be quickly formed, resulting in lower water requirements during casting. Further mixing with aluminate cement ensures that cement, as the cementing phase, is uniformly distributed throughout the system. This uniform phase distribution provides the high-strength, wear-resistant, and refractory castable with a more controllable hardening process, higher bulk density and strength, and superior high-temperature wear resistance.
[0084] (3) This invention premixes lithium chloride with aluminate cement, causing the cement particles to be uniformly coated with lithium chloride. During the hydration reaction, a large number of lithium ions are released into the water, reacting rapidly with dissolved aluminate ions to form an unstable, water-insoluble intermediate phase. This intermediate phase then decomposes in an alkaline environment rich in calcium ions to generate crystal nuclei, precisely controlling the hydration path of the aluminate cement to directly generate a stable C3AH6 phase. The biggest hidden danger of traditional processes is the formation of a large number of metastable hydration products. When the subsequent temperature exceeds 30-35°C, a reaction occurs, leading to a significant decrease in intermediate-temperature strength. The high-strength, wear-resistant, and refractory castable prepared by this invention will not experience strength degradation due to crystal transformation throughout its entire service life. The microstructure of the stable C3AH6 phase has a more uniform and interconnected pore distribution, greatly improving the strength and wear resistance of the high-strength, wear-resistant, and refractory castable. At the same time, it makes the hydration reaction during the curing process controllable and reduces production costs. The prepared high-strength, wear-resistant, and refractory castable has excellent intermediate-temperature strength.
[0085] Water was added to the high-strength wear-resistant refractory castable at a mass ratio of 100:4wt% to water, mixed thoroughly, cast into molds, cured at room temperature, and dried at 110℃ for 24 hours. The service temperature range was 900~1100℃. The main properties of the high-strength wear-resistant refractory castable were tested: wear resistance ≤2.5cm. 3 (900℃×3h), compressive strength at room temperature ≥75MPa after heat treatment at 110℃, ≥125MPa after heat treatment at 900~1100℃; flexural strength at room temperature ≥15MPa after heat treatment at 110℃, ≥18MPa after heat treatment at 900~1100℃; thermal shock resistance ≥30 cycles (900℃, water cooling); permanent linear change after heating ±0.5% (1000℃×3h); thermal conductivity ≥6W·(m·K). -1 (1000℃), bulk density ≥2.6 g·cm³ -3 .
[0086] The test standards for the performance indicators involved in this specific embodiment are as follows: abrasion resistance is measured according to GB / T18301-2012; high temperature abrasion resistance is measured according to ISO 16349:2015; bulk density is measured according to GB / T2997-2015; thermal shock stability is measured according to GB / T30873-2014; permanent linear change upon heating is measured according to GB / T5988-2022; compressive strength is measured according to GB / T5072-2023; flexural strength is measured according to GB / T3001-2017; and thermal conductivity is measured according to GB / T5990-2021.
[0087] Therefore, this specific embodiment has low production cost, and the high-strength wear-resistant refractory castable prepared has the characteristics of high compressive strength, excellent high-temperature wear resistance, high medium-temperature strength, and controllable hydration process.
Claims
1. A method for the preparation of high-strength, wear-resistant, refractory castable, characterized in that The steps of the preparation method are: Step 1, 5-7 parts by mass of α-active alumina micro-powder, 5-7 parts by mass of silicon carbide micro-powder, 4-5 parts by mass of silica micro-powder and 9-12 parts by mass of white corundum micro-powder are added into a ball mill tank, and ball milling is carried out at a rotation speed of 45-50 rpm for 3-6 h, and then screening is performed to obtain premixed powder with a particle size of <45 μm; Step 2, 0.1-0.15 parts by mass of sodium tripolyphosphate, 0.05-0.1 parts by mass of sodium hexametaphosphate, 0.05-0.1 parts by mass of FDN, 0.4-0.45 parts by mass of lithium chloride micro-powder and 8-14 parts by mass of aluminate cement are added into a ball mill tank, and ball milling is carried out at a rotation speed of 45-50 rpm for 3-6 h to obtain premixed cement; Step 3, 20-25 parts by mass of bauxite particles with a particle size of 3-5 mm, 25-30 parts by mass of bauxite particles with a particle size of 1-3 mm and 10-15 parts by mass of bauxite particles with a particle size of <1 mm are added into a stirring pot, and dry mixing is carried out to obtain premixed aggregate; Step 4, the premixed cement and the premixed powder are added into the premixed aggregate, and 1-2 parts by mass of steel fiber is further added, and dry mixing is continued for 120-180 s to obtain high-strength wear-resistant refractory castable.
2. A process for the preparation of high strength abrasion and fire resistant castable according to claim 1, characterized in that, The α-active alumina micro-powder has a particle size of <1 μm, and the Al2O3 content of the α-active alumina micro-powder is ≥99.5 wt%.
3. The process for the preparation of high strength abrasion and fire resistant castable as claimed in claim 1 wherein, The silicon carbide micro-powder has a particle size of <50 μm, and the SiC content of the silicon carbide micro-powder is ≥95 wt%.
4. The process for the preparation of high strength abrasion and fire resistant castable according to claim 1, characterized in that, The silica micro-powder has a particle size of <0.15 μm, and the SiO2 content of the silica micro-powder is ≥85 wt%.
5. The process for the preparation of high strength abrasion and fire resistant castable as claimed in claim 1 wherein, The white corundum micro-powder is plate-like white corundum or electro-fused white corundum, the particle size of the white corundum micro-powder is ≤75 μm, and the Al2O3 content of the white corundum micro-powder is ≥99 wt%.
6. The process for the preparation of high strength abrasion and fire resistant castable according to claim 1, characterized in that, The lithium chloride micro-powder has a particle size of ≤150 μm, and the LiCl content of the lithium chloride micro-powder is ≥99 wt%.
7. The process for the preparation of high strength abrasion and fire resistant castable as claimed in claim 1 wherein, The bauxite particles have an Al2O3 content of >85 wt%.
8. A process for the preparation of high strength abrasion and fire resistant castable as claimed in claim 1, wherein, The aluminate cement has a particle size of <45 μm accounting for <8 wt%, and a refractoriness of 1420-1460 ℃; the Al2O3 content of the aluminate cement is ≥51 wt%, and the CaO content is ≥33.5 wt%.
9. The process for the preparation of high strength abrasion and fire resistant castable according to claim 1, characterized in that, The steel fiber is single bulk type without plating, longitudinally straight, with hooks at both ends, smooth surface, length of 27-33 mm, equivalent diameter of 0.28-0.32 mm, and tensile strength of 1000-1300 Mpa.
10. A high strength abrasion resistant refractory castable characterized in that The high-strength wear-resistant refractory castable is prepared according to the preparation method of the high-strength wear-resistant refractory castable in any one of claims 1-9.
Citation Information
Patent Citations
High-alumina high-temperature fire-resistance casting material and preparation method thereof
CN102731123A
High-wear-resistance quick-drying refractory castable and preparation method thereof
CN111362676A
Al2O3-SiC-C refractory castable and preparation method thereof
CN111646784A
ZrO2-(Al, Cr) 2O3-Mg (Al, Cr) 2O4 composite refractory material and preparation method thereof
CN117326862A